The gut hormone GIP predicts CV prognosis in patients with acute myocardial infarction. (14th October 2021) - Kahles, F; Rueckbeil, M V; Arrivas, M C; Mertens, R W; Moellmann, J; Biener, M; Giannitsis, E; Katus, H A; Marx, N; Lehrke, M
Abstract: Background: The gut incretin hormones GLP-1 (glucagon-like peptide-1) and GIP (glucose-dependent insulinotropic peptide) are secreted by enteroendocrine cells following food intake leading to insulin secretion and glucose lowering. Beyond its regulatory effects in glucose metabolism activation of the GLP-1 receptor has been found to improve cardiovascular prognosis in patients with diabetes and high cardiovascular risk. The functional relevance of GIP (the other main incretin) in patients with cardiovascular disease is largely unknown. The aim of this study was to assess the predictive capacity of GIP serum levels for cardiovascular outcome in patients with acute myocardial infarction. Methods and results: We investigated the predictive value of GIP serum levels at the time of hospital admission for cardiovascular prognosis in a cohort of 852 patients (67±13 years; 73% men) with acute myocardial infarction (34% STEMI, 66% NSTEMI). Kaplan-Meier curves (GIP median; cut-off: 69 pg/mL) and univariable Cox regression analyses showed that lower GIP levels were associated with an increased cardiovascular mortality (HR of logarithmized GIP values: 0.520; 95% CI: 0.30–0.90; p=0.020). After adjustment for age, sex, smoking, hypertension, hypercholesterolemia, diabetes and family history of cardiovascular disease the association between GIP levels and cardiovascular mortality remained significant with similar hazard ratios as in the univariable Cox regression model. Conclusion: In summary, we found lower GIP levels to independently predict a poor cardiovascular outcome in high-risk patients with acute myocardial infarction. Future larger studies are needed to foster our understanding of the gut - heart axis as a yet fairly neglected field of system biology and to elucidate whether the GIP system might open novel therapeutic approaches for the treatment of patients with cardiovascular disease. Funding Acknowledgement: Type of funding sources: None.